2016
DOI: 10.11648/j.ajac.20160401.14
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Friendly Reduction of Aromatics to Alicyclic Compounds at Room Temperature Using Superactive Calcined Ni-Al Hydrotalcite Catalysts

Abstract: Calcined Ni-Al hydrotalcite (HT) 2: 1, Cat. A, is a superactive catalyst for reduction of substituted aromatics, i. e. toluene, benzene, nitrobenzene, chloro-, bromo-, and iodobenzene to their respective alicyclic products at room temperature in the presence of molecular hydrogen. Cat. A attained higher conversions compared to calcined Ni-Al hydrotalcites with ratios of 2.5: 1, and 3: 1. Calcined Ni-Al HT is a superactive catalyst whereas catalysts Niγ-Al 2 O 3 or Ni-SiO 2 with Ni contents of 2%, 5%, and 10% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Ni-hydrotalcite catalysts for reductive amination of benzaldehyde with NaBH4, acts as reducing agent to form in situ-Ni-boride which is generated swiftly in the formation of desired product at room temperature. The activity of Ni-Al hydrotalcites for organic transformation discussed above is attributed due to the even distribution of Ni ions for 2:1 ratio of Ni-Al hydrotalcite catalysts and inactivity of 2.5:1, and 3:1 ratio catalyst is due to higher content of Ni in Ni-Al hydrotalcite [107].…”
Section: Reductive Amination Of Benzaldehyde With Ni-al Ldhsmentioning
confidence: 90%
See 1 more Smart Citation
“…Ni-hydrotalcite catalysts for reductive amination of benzaldehyde with NaBH4, acts as reducing agent to form in situ-Ni-boride which is generated swiftly in the formation of desired product at room temperature. The activity of Ni-Al hydrotalcites for organic transformation discussed above is attributed due to the even distribution of Ni ions for 2:1 ratio of Ni-Al hydrotalcite catalysts and inactivity of 2.5:1, and 3:1 ratio catalyst is due to higher content of Ni in Ni-Al hydrotalcite [107].…”
Section: Reductive Amination Of Benzaldehyde With Ni-al Ldhsmentioning
confidence: 90%
“…Rahman et al [107] reported the reduction of aromatics to alicyclic molecules with super active 2:1 Ni-Al hydrotalcite catalysts to alicyclic without loss of activity of the catalysts. Osmate intercalated hydrotalcite aimed at selective oxidative bromination of bisphenol-A for asymmetric dihydroxylation of olefins [108] with NMO (N-Methylmorpholine N-oxide) used as co-oxidant in company of molecular oxygen was reported by Choudhary et al [108].…”
Section: Reduction Of Aldehydes To Alcohols With Ni-almentioning
confidence: 99%